Closing the publishing gender gap in economics and political science: Does a critical mass matter? - Daniel Stockemer; Gabriela Galassi; Engi Abou-El-Kheir (PLoS ONE, 2025)
Using novel data on publications and citations by researchers in economics and political science in top 50 universities globally, we analyze the relationship between female representation and the gender gap in research output and impact. Using the concepts of substantive representation and critical mass, we expect that the average female researcher in departments with more women publishes more and receives more citations than the average female researcher in universities with a lower share of female faculty. Comparing women’s publication and citation performance for the top 50 universities across the globe relative to men’s, we find support for these expectations. We find that female researchers’ performance matches that of their male counterparts in balanced departments, which are more common in political science. In contrast, the link between female performance and representation is weaker in departments with little gender balance, which are more typical in economics. These findings highlight the importance of reaching a critical mass of female representation to close gender gaps in research output and impact.